Numerical study on the effect of tangential intake on vortex dropshaft assessment using pressure distributions - Lu Chang (Engineering Applications of Computational Fluid Mechanics, 2022)
Dropshafts with tangential intakes are common structures in urban water drainage systems. The plunging and vortex flowpatterns are the typical flow regimes, which are mainly affected by the tangential intake design and flood discharge. However, thehydraulic flow transition between vortex and plunging flow patterns has received little attention, which may affect the dropshaftoperation during extreme flood discharge events. In this study, the effects of the flow discharge and contraction ratio on the pressuredistributions of vortex dropshafts are analysed based on a series of numerical simulations. The pressure distributions of the plungingand vortex flow patterns are compared; two hydraulic factors are used to distinguish rotational and non-rotational dropshaftoperations. For appropriate vortex dropshaft designs, the minimum to maximum wall pressure ratio should be greater than 0.1 at theintake cross-section and greater than 0.2 during the falling process. Based on this principle, flows in the annular dropshaft areclassified into non-rotation, transition, and rotation regimes. The results agree with the theoretical rotation intensity of the vortex flow,and an empirical relation is proposed. The present study is easy to implement and practically useful to assess the vortex dropshaftdesign for local water drainage systems.